Mediterranean climate variability during the Holocene - CASFORD, J.S.L.; ABU-ZIED, R.; ROHLING, E.J.; COOKE, S.; BOESSENKOOL, K.P.; BRINKHUIS, H.; DE VRIES, C.; WEFER, G.; GERAGA, M.; PAPATHEODOROU, G.; CROUDACE, I.; THOMSON, J.; et al. (Mediterranean Marine Science, 2001)
We present a study on four high sedimentation-rate marine cores with suppressed bioturbation effects, recovered along the northern margin of the eastern Mediterranean. We demonstrate that this region, central to the development of modern civilisation, was substantially affected throughout the Holocene by a distinct cycle of cooling events on the order of 2o C. In the best-preserved cases the onset of these events appears particularly abrupt, within less than a century. The cooling events typically lasted several centuries, and there are compelling indications that they were associated with increased aridity in the Levantine/NE African sector (Rossignol-Strick, 1995; 1998; Alley et al., 1997; Hassan, 1986; 1996; 1997a,b; McKim Malville et al., 1998). Several of these episodes appear coincident with cultural reorganisations, with indigenous developments (eg. cattle domestication, new technologies) and population migrations and fusion of peoples and ideas (Hassan, 1986; 1996; 1997a,b; McKim Malville, 1998). We infer that climatic events of a likely high-latitude origin (O’Brien et al., 1995; Bond et al., 1997; Mayewski et al., 1997; Alley et al., 1997) caused cooling and aridity in and around the eastern Mediterranean via a direct atmospheric link, and therefore played an important role in the development of modern civilisation.